Preparation and Photocatalytic Activity of Cu2O/Nickel-Zinc Ferrite Magnetic Photocatalyst - Li, Yan; Chen, Wei; Chen, Yuanyuan; Xu, Haiyan; Xu, Ling (Asian Journal of Chemistry, 2012)
Nickel-zinc ferrite powders were prepared by EDTA-complexing method, Cu2O/nickel-zinc ferrite magnetically separable photocatalyst was prepared by the hydrazine hydrate reduction method. The as-prepared sample was characterized by X-ray diffraction, high resolution transmission electron microscopy, Fourier transform infrared spectroscopy, the photocatalytic activity of the sample was evaluated by degradation of methyl orange under the UV illumination. The results show that the Cu2O coating nickel-zinc ferrite is cubic structure. Cu2O/nickel-zinc ferrite powders have photocatalytic activity under the irradiation of ultraviolet light, the Cu2O/nickel-zinc ferrite powders still have magnetic property and can be separated from the system by applying magnetic field.